Precision Product-Process Design and Optimization Select Papers from AIMTDR 2016 - Pande, Sanjay S.; Dixit, Uday S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book introduces readers to various tools and techniques for the design of precision, miniature products, assemblies and associated manufacturing processes. In particular, it focuses on precision mechanisms, robotic devices and their control strategies, together with case studies. In the context of manufacturing process, the book highlights micro/nano machining/forming processes using non-conventional energy sources such as lasers, EDM (electro-discharge machining), ECM (electrochemical machining), etc. Techniques for achieving optimum performance in process modeling, simulation and optimization are presented. The applications of various research tools such as FEM (finite element method), neural networks, genetic algorithms, etc. to product-process design and optimization are illustrated through case studies. The state-of-the-art material presented here provides valuable directions for product developmentand future research work in this area. The contents of this book will be of use to researchers and industry professionals alike.
PART I: Precision Product Design and Control -- Optimal Design of a Stewart-Gough Platform for Multi- Directional Additive Manufacturing -- Task level Planning and Implementation of Robotic Assembly Under Machine Vision Guidance -- Position and Impedance Control of a Multi-Finger Tendon-Driven Robotic Hand -- A Piezoelectric Actuator Based Compact Micro Manipulation System for Robotic Assembly -- Experimental Studies and Numerical Simulations of a Displacement Amplifying Compliant Mechanism -- PART II: Process Modelling and Optimization -- Numerical Modelling of SLM Additive Manufacturing for Magnesium Alloy -- Finite Element Analysis of Residual Stress in Selective Laser Melting of Ti6Al4V Powder Layer -- Parametric Optimization of 3D Printing Process using MCDM Method -- Towards Development of an Intelligent PCD Insert Clock Testing Method and Prediction of Product Performance -- Focused Ion Beam Fabrication: Process Development and Optimization Strategy for Optical Applications -- Machining Guidelines for Fabricating Microgrooves of Varied Cross-sections by Electrochemical Micromachining -- Multi Response Optimization of Powder Mixed EDM Machining Parameters Using Taguchi Based TOPSIS Method -- Optimization of Single Pitch Error and MRR in a WEDM Gear cutting Process Using MOORA Method -- Abrasive Flow Nano Finishing of High Aspect Channels using Different Polymer Rheological Abrasive Medium -- Optimizing Toolpath Generation in Magnetic Field Assisted Finishing Process During Nanofinishing of Biomaterials -- Study of Surface Integrity in Conventional and Ultrasonic Assisted Turning with Self -lubricating Cutting Inserts -- Parametric Analysis and Optimization of Surface Finish During Microtexturing on Titanium Using Pulsed Nd YAG Laser -- A Novel Approach for Prediction and Calculation of Sheet Thinning in Incremental Sheet Forming -- Optimum allocation of machines with multiple objectives using NSGA-II.
Keywords: Manufactures; Engineering design; Security systems; Machines, Tools, Processes; Engineering Design; Security Science and Technology